Exposure to artificial light at night: A common link for obesity and cancer?. (September 2022) - Muscogiuri, Giovanna; Poggiogalle, Eleonora; Barrea, Luigi; Tarsitano, Maria G.; Garifalos, Francesco; Liccardi, Alessia; Pugliese, Gabriella; Savastano, Silvia; Colao, Annamaria; ,; Colao, Annamaria; Alviggi, Carlo; et al.
Abstract: Exposure to artificial light at night (ALAN) has been associated with disruption of the circadian system, which has been pointed out to have detrimental effects on health. Exposure to outdoor ALAN is very frequent in industrialised countries due to nocturnal light pollution and the relevant involvement of the total workforce in shift work and night work. Ecological and epidemiologic studies highlight the association between exposure to ALAN and several diseases, mainly obesity and cancer. More recently, also indoor ALAN exposure has been investigated. Among several multifactorial mechanisms linking ALAN exposure and health risks, suppression of melatonin secretion plays a pivotal role leading to alterations in circadian rhythm patterns, that are detrimental in terms of appetite regulation, and dysfunctions in metabolic signalling and cell growth in cancer. In addition, gut dysbiosis, inflammation, hypovitaminosis D, imbalance in cytokine secretion and levels are responsible for the multiple relationship linking circadian dysregulation due to ALAN exposure and obesity, and cancer. Therefore, the current manuscript summarises human and basic studies pointing out the impact of ALAN exposure on health, mostly focusing on obesity and cancer. Based on extant evidence, prevention strategies for obesity and cancer should be prompted, targeting exposure to ALAN. Highlights: Exposure to artificial light at night is a determinant in the pathogenesis of cancer and obesity. Circadian disruption represents risk factor for cancer and obesity. Domestic artificial light at night is risk factor for metabolic alterations.